Social media Platforms: Exposing students to cybercrimes - Edey P. Agara; Felix E. Ojong; Josephat O. Emeka; A. M. Ogaboh Agba; Abayomi I. Akintola; Olumayowa V. Ogunsola (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
Today, social media becomes the order of the day in which all aspect of life is affected. The study therefore examines the phenomenon of social media use and students' exposure to cybercrimes in Nigeria. Students’ exposure to Facebook, Instagram, Twitter, and WhatsApp applications were considered. A cross-sectional survey was conducted on 900 students drawn from Cross River State, Nigeria. Data were retrieved using questionnaire and Focus Group Discussion (FGD). Descriptive analysis for the study revealed that Facebook use, Instagram use, and Twitter use significantly expose students to cybercrimes. The study concluded that social media use, as beneficial as it is, has potential dangers that could impose undesirable costs on users. It was thus recommended among others that the users of social media must carefully determine the information they put on social media to avoid providing explicit personal details that can be used by hackers against them. Furthermore, government must enact appropriate legislation or enforce existing laws to checkmate the activities of cybercriminals in society.